2020
DOI: 10.3390/ani10122383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold Exposure on Some Physiological, Productive, and Metabolic Variables in Lactating Dairy Goats

Abstract: Low winter temperatures in some regions have a negative impact on animal performance, behavior, and welfare. The objective of this study was to evaluate some physiological, metabolic, and lactational responses of dairy goats exposed to cold temperatures for 3 weeks. Eight Murciano-Granadina dairy goats (41.8 kg body weight, 70 days in milk, and 2.13 kg/day milk) were used from mid-January to mid-March. Goats were divided into 2 balanced groups and used in a crossover design with 2 treatments in 2 periods (21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Furthermore, the gene expressions involved in metabolic pathways, transportation pathways, and protein biosynthesis were affected concomitantly. Furthermore, there was little overlap among the metabolites identified in this study when compared to the cold stress responses in the urine samples of rats under both acute and chronic cold stress patterns [ 23 , 25 , 44 ], in the liver of yellow drum [ 45 ], and in the blood of dairy goats [ 46 ] exposed to cold stress. These studies reveal the diversity of metabolic regulation under cold conditions due to the differences presented in experimental species, detection platform, and the degree and intensity of the cold treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gene expressions involved in metabolic pathways, transportation pathways, and protein biosynthesis were affected concomitantly. Furthermore, there was little overlap among the metabolites identified in this study when compared to the cold stress responses in the urine samples of rats under both acute and chronic cold stress patterns [ 23 , 25 , 44 ], in the liver of yellow drum [ 45 ], and in the blood of dairy goats [ 46 ] exposed to cold stress. These studies reveal the diversity of metabolic regulation under cold conditions due to the differences presented in experimental species, detection platform, and the degree and intensity of the cold treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Cold stress can reduce the growth performance of animals, such as BW and feed efficiency [ 57 , 58 , 59 ]. In the present study, the chicks supplemented with EUE showed better growth performance of higher BW ( p < 0.01) and ADG ( p < 0.05) and lower F/G ( p < 0.001) throughout the study period, and higher AFI at 0–7 d ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in feed intake [25], decrease in water intake [20] Use of high-quality forage or pastures Fat supplementation in ration Adlib warm water 4. Production Decrease in milk production, increase in body wool, hair and fleece [26].…”
Section: Nutritionalmentioning
confidence: 99%
“…There is also a concomitant decrease in rectal temperature. The levels of hemoglobin concentration (Hb), packet cell volume (PCV), total erythrocyte counts (TEC) and total leucocyte count (TLC) are higher during winter and lower during summer [16][17][18][19][20]. It has also been observed that the levels of Hb, PCV and TEC are higher in breeds adaptated to cold hilly climate due to low level of oxygen concentration and higher Hb and TEC counts help to meet up the oxygen requirement in the body [16,21,22].…”
Section: Effects Of Cold Stress On General Physiology and Productivit...mentioning
confidence: 99%
See 1 more Smart Citation